ENTREPRENEURIAL UNIVERSITY IN KAZAKHSTAN SOCIAL AND ECONOMIC LANDSCAPE (Journal of Economic Research & Business Administration, 2018)
The problems of entrepreneurial universities formation in the Republic of Kazakhstan are consideredin this article, the analysis of the theoretical and methodological base of the research subject is presented,and the current state of Kazakhstan practice is described. The purpose of the work is to considerthe real difficulties of transforming Kazakh universities into entrepreneurial ones and to offer solutions forthese problems on the basis of a detailed analysis of the progressive practice of creating entrepreneurialuniversities.The methodological basis of the work is made up of such general economic methods as the methodof dialectical and historical materialism, the method of induction and deduction, methods of statisticalanalysis, namely the collection and grouping of statistical data.The results of the study allowed the authors to conclude that the implemented model of the entrepreneurialuniversity should take into account the institutional features of the country and the possibilitiesof the university. At the same time, an important component of their successful activity is the availabilityof highly qualified managers and teachers who have an entrepreneurial vision and idea, creativethinking, the pursuit of success, a willingness to take risks without fear of changes.The scientific and practical value of the work is that the recommendations contained in it will allowimproving management approaches in the creation of entrepreneurial universities. Therefore, they willmake it possible to take a serious step in the development of the domestic market for science-intensiveproducts and the provision of resources for higher education, and will contribute to the modernizationof the entire Kazakh economy.